Determination of climatologically suitable places in the Midwest for feedlot cattle production by using the comprehensive climate index model - Koknaroglu, H.; Harrington Jr, John; Mader, T. L. (My University, 2016)
The objective of this study was to determine climatologically suitable places to raise feedlot cattle in the Midwest. Hourly average temperature, relative humidity, and wind speed values for 22 locations (Des Moines, Mason City, Sioux City, Waterloo, Concordia, Dodge City, Goodland, Russell, Topeka, Wichita, Columbia, Kansas City, KCI, Springfield, St. Louis, Grand Island, Lincoln, Norfolk, North Platte, Omaha, Scottsbluff, and Valentine), spanning the last 10 yr, were obtained. Daily solar radiation values could not be obtained from the weather stations and were calculated based on a formula that takes hemisphere, latitude, and day of the year into account. The comprehensive climate index (CCI) model was used to predict DMI, ADG, and feed efficiency of feedlot cattle. The CCI enables one to quantify beef cattle performance for a number of breeds based on environmental conditions (temperature, relative humidity, wind speed, and solar radiation) at any time in the year. Because mostly beef cattle breed calves are placed into the feedlot in the Midwest, the British (beef breed) option in CCI was chosen to calculate the maintenance energy requirement of cattle. It was assumed that calves would be placed on feed at 340 kg and be marketed at 613 kg and that diets would have 3200 kcal/kg metabolic energy and would have DMI of 2.10% of the BW. Results comparing the 22 locations showed that Mason City had the highest and Columbia had the lowest DMI (P < 0.05). Cattle raised in Kansas and Missouri had lower DMI than those raised in Iowa and Nebraska. Cattle had ADG ranging from 1.74 to 1.69 kg/d; Scottsbluff and Goodland had the highest ADG and Columbia had the lowest ADG (P < 0.05). As it is observed in DMI, cattle raised in south latitudes had lower ADG than those raised in northern latitudes. Springfield and Wichita had better feed efficiency than other locations, and Mason City had the worst feed efficiency. Cattle raised in Kansas and Missouri had better feed efficiency than those raised in Iowa and Nebraska (P < 0.05). Results showed that there are differences in terms of performance of cattle raised in different locations in the Midwest and this should be taken into consideration for economical beef production.
Citation: Koknaroglu, H., Harrington, J. A., & Mader, T. L. (2016). Determination of climatologically suitable places in the Midwest for feedlot cattle production by using the comprehensive climate index model. Journal of Animal Science, 94, 28-29. doi:10.2527/msasas2016-062
Keywords: Comprehensive Climate Index; Feedlot; Performance; Agriculture